2008
DOI: 10.1091/mbc.e08-02-0188
|View full text |Cite
|
Sign up to set email alerts
|

Calnexin Is Involved in Apoptosis Induced by Endoplasmic Reticulum Stress in the Fission Yeast

Abstract: Stress conditions affecting the functions of the endoplasmic reticulum (ER) cause the accumulation of unfolded proteins. ER stress is counteracted by the unfolded-protein response (UPR). However, under prolonged stress the UPR initiates a proapoptotic response. Mounting evidence indicate that the ER chaperone calnexin is involved in apoptosis caused by ER stress. Here, we report that overexpression of calnexin in Schizosaccharomyces pombe induces cell death with apoptosis markers. Cell death was partially depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 104 publications
(257 reference statements)
5
75
8
Order By: Relevance
“…Recently, we reported that the cytosolic tail of calnexin is involved in mediating an ER-stress-induced apoptotic signal (Guerin et al, 2008). Further characterization of this apoptotic pathway and investigation of the cellular function of Cif1p will reveal whether an apoptotic mechanism and the Cin epigenetic state are functionally linked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that the cytosolic tail of calnexin is involved in mediating an ER-stress-induced apoptotic signal (Guerin et al, 2008). Further characterization of this apoptotic pathway and investigation of the cellular function of Cif1p will reveal whether an apoptotic mechanism and the Cin epigenetic state are functionally linked.…”
Section: Discussionmentioning
confidence: 99%
“…Cif1p-Venus fusion imaging was performed as described (Guerin et al, 2008). Microscopy analysis was performed with a fluorescence inverted microscope (Nikon TE2000U).…”
Section: Microscopy Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…4A to C). Next, we analyzed the expression of calnexin, a chaperone previously associated with stress-induced apoptosis (57,58). Immunofluorescence analysis demonstrated significantly higher levels of expression of calnexin in PTCs from Ctns Ϫ/Ϫ mouse kidneys (see Fig.…”
Section: Cystinotic Cells Have Decreased Rab27a Expressionmentioning
confidence: 99%
“…Thirty-two genes among 2,449 genes in S. pombe show Homology to heat shock proteins. There were a few functional studies of the fission yeast chaperone such as calnexin (13), cdc37 (14), and Hsp90/Git10 (15), Rsp1p (16), ASF1/CIA1 (17). In our lab, for screening of molecular chaperones without an α-crystalline domain from S. pombe, heat stable proteins were screened from the fission yeast and examined their anti-aggregation activity using the yeast citrate synthase.…”
Section: Introductionmentioning
confidence: 99%